The Impact of International Business Strategy Simulation Games on Student Engagement. (June 2019) - Rogmans, Tim; Abaza, Wasseem
Background . Despite the increasing use of business simulation games in management education little is known about theireffectiveness as learning tools . Aim . The aims of this study were to assess the effectiveness of an international business simulation game in enhancing levels of student engagement. Methods . We investigated student engagement levels after using a simulation game, as measured through quantitative self-reports obtained through a survey among students. The results were compared to engagement levels experienced in more traditional classroom based case discussions with the same students in the same course. The study was carried out across six class sections taught by two professors over two semesters. Results . The results show that average student engagement levels were higher during the traditional case study class than during the class using the simulation game. The standard deviation of the reported levels of student engagement was higher for the simulation game than for the traditional class, indicating that student responses were more extreme (either positive or negative) for the class using the simulation game. Students who were generally more motivated to learn reported higher levels of engagement with the simulation, whereas students with low levels of motivation who found the game complex became less engaged. Conclusion . Simulation games arenot always necessarily effective in enhancing engagement among all students. The choice between traditional and experiential learning methods may be partly determined on the basis of the level ofstudent motivation and otherstudent characteristics .